The role of the gut microbiota and probiotics associated with microbial metabolisms in cancer prevention and therapy - Wang, Zijun; Li, Lanqing; Wang, Shunshun; Wei, Jing; Qu, Linghang; Pan, Lianhong; Xu, Kang (Frontiers in Pharmacology, 2022)
Cancer is the second leading cause of elevated mortality worldwide. Thus, the development of drugs and treatments is needed to enhance the survival rate of the cancer-affected population. Recently, gut microbiota research in the healthy development of the human body has garnered widespread attention. Many reports indicate that changes in the gut microbiota are strongly associated with chronic inflammation-related diseases, including colitis, liver disease, and cancer within the intestine and the extraintestinal tract. Different gut bacteria are vital in the occurrence and development of tumors within the gut and extraintestinal tract. The human gut microbiome has significant implications for human physiology, including metabolism, nutrient absorption, and immune function. Moreover, diet and lifestyle habits are involved in the evolution of the human microbiome throughout the lifetime of the host and are involved in drug metabolism. Probiotics are a functional food with a protective role in cancer development in animal models. Probiotics alter the gut microbiota in the host; thus, beneficial bacterial activity is stimulated, and detrimental activity is inhibited. Clinical applications have revealed that some probiotic strains could reduce the occurrence of postoperative inflammation among cancer patients. An association network was constructed by analyzing the previous literature to explore the role of probiotics from the anti-tumor perspective. Therefore, it provides direction and insights for research on tumor treatment.